Financial Knowledge and the Gender Gap - Ann Woodyard; Cliff Robb (Journal of Financial Therapy, 2012)
Financial knowledge has been identified as an issue of importance to individual financial wellness. The FINRA Financial Capability Study provides data that make it possible to assess financial knowledge, and to analyze it in the context of financial satisfaction and participation in financial behaviors that are generally considered positive. This paper looks at these relationships by gender and by age group, identifying key differences in outcomes and behaviors. The aim of this study was to identify areas and issues where policy makers can focus efforts, and where practitioners can develop education and therapy protocols to assist clients in financial development and restoration.
Keywords: financial therapy; financial education